2014
DOI: 10.1097/rct.0000000000000149
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Features of Papillary Thyroid Carcinomas

Abstract: The study results demonstrated that the most common CT features of PTCs included homogenous low attenuation, a taller-than-wide shape, no calcifications, and homogeneous decreased enhancement and that CT was inferior to US for evaluating nodular shape and calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 11 publications
4
19
1
Order By: Relevance
“…On thyroid ultrasonography, anteroposterior and transverse diameters of the nodule are parallel with anteroposterior and transverse axes of the thyroid gland, respectively [17]. In a recent CT study of papillary thyroid carcinoma [15], the assessment of nodular shape revealed a significant difference between ultrasound and CT, but the nodular shape evaluation method in CT was different from the present study. In addition, the present study did not involve the measurement of longitudinal diameter of thyroid nodules.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…On thyroid ultrasonography, anteroposterior and transverse diameters of the nodule are parallel with anteroposterior and transverse axes of the thyroid gland, respectively [17]. In a recent CT study of papillary thyroid carcinoma [15], the assessment of nodular shape revealed a significant difference between ultrasound and CT, but the nodular shape evaluation method in CT was different from the present study. In addition, the present study did not involve the measurement of longitudinal diameter of thyroid nodules.…”
Section: Discussioncontrasting
confidence: 91%
“…Consequently, it is still unclear whether CT aids the diagnosis of thyroid incidentaloma. Recently, one study demonstrated that the most common CT features for papillary thyroid carcinoma included homogeneous low attenuation, a taller-than-wide shape, absence of calcifications, and homogeneous decreased enhancement [15]. In the present study, the most common CT features of both FTA and FTC included low attenuation, intraglandular configuration, smooth margin, round shape, and absence of calcifications.…”
Section: Discussionsupporting
confidence: 61%
“…These included the presence or absence of calcification and necrosis and heterogeneous or homogeneous attenuation. 15,21 ATC contained calcification and necrosis and had heterogeneous attenuation. Thyroid lymphoma, in contrast, was homogeneous without calcification or necrosis.…”
Section: Discussionmentioning
confidence: 98%
“…Calcifications may be seen in both papillary thyroid cancer (32%) and ATC (62% in our cohort). 21 Thyroid lymphoma typically presents with a rapidly enlarging anterior neck mass and symptoms of mass effect, similar to ATC. Differentiation of lymphoma from ATC is important for both prognosis and treatment implications, and when this rare entity is suspected, flow cytometry can be performed on a fresh fine-needle aspiration sample for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation